Implications of Three-Dimensional Cell Culture in Cancer Therapeutic Research - Poornima, Kolluri; Francis, Arul Prakash; Hoda, Muddasarul; Eladl, Mohamed Ahmed; Subramanian, Srividya; Veeraraghavan, Vishnu Priya; El-Sherbiny, Mohamed; Asseri, Saad Mohamed; Hussamuldin, Abdulrahman Bashir Ahmed; Surapaneni, Krishna Mohan; Mony, Ullas; Rajagopalan, Rukkumani (Frontiers in Oncology, 2022)
Replicating the naturalistic biomechanical milieu of cells is a primary requisite to uncover the fundamental life processes. The native milieu is significantly not replicated in the two-dimensional (2D) cell cultures. Alternatively, the current three-dimensional (3D) culture techniques can replicate the properties of extracellular matrix (ECM), though the recreation of the original microenvironment is challenging. The organization of cells in a 3D manner contributes to better insight into the tumorigenesis mechanism of the in vitro cancer models. Gene expressions studies are susceptible to alterations in their microenvironment. Physiological interactions among neighboring cells also contribute to gene expression, which is highly replicable with minor modifications in 3D cultures. 3D cell culture provides a useful platform for further identifying the biological characteristics of tumor cells, particularly in the drug sensitivity area of the key points of translational medicine. It promises to be a bridge between traditional 2D culture and animal experiments and is of great importance for further research in tumor biology. Some of the barriers interfering while observing the live cells growing in a natural 3D physiological environment can be addressed by the current new imaging technology and implementation of standard protocols.